Photoredox Catalyzed Single C−F Bond Activation of Trifluoromethyl Ketones: A Solvent Controlled Divergent Access of gem‐Difluoromethylene Containing Scaffolds - Ghosh, Soumen; Qu, Zheng‐Wang; Roy, Sourav; Grimme, Stefan; Chatterjee, Indranil (Chemistry : a European journal, 2023)
Selective defluorinative functionalization of trifluoromethyl ketones is a long‐standing challenge owing to the exhaustive mode of the process. To meet the demands for the installation of the gem‐difluoromethylene unit for the construction of the molecular architectures of well‐known pharmaceuticals and agrochemicals, a distinct pathway is thereby highly desirable. Here, a protocol is introduced that allows the divergent synthesis of gem‐difluoromethylene group containing tetrahydrofuran derivatives and linear ketones via single C−F bond activation of trifluoromethyl ketones using visible‐light photoredox catalysis in the presence of suitable olefins as trapping partner. The choice of appropriate solvent and catalyst plays a significant role in controlling the divergent behavior of this protocol. Highly reducing photo‐excited catalysts are found to be responsible for the generation of α,α‐difluoromethyl ketone (DFMK) radicals as the key intermediate via a SET process. This protocol also results in a high diastereoselectivity towards the formation of partially fluorinated cyclic ketal derivatives with simultaneous construction of one C−C and two C−O bonds. State‐of‐the‐art DFT calculations are performed to address the origin of diastereoselectivity as well as the divergence of this protocol. Single and selective C−F bond activation of trifluoromethyl ketones using visible‐light photoredox catalysis is achieved in a divergent fashion. Trapping of photo‐catalytically generated difluoromethyl radical to various styrene derivatives benefitted with the formation of two essential classes of difluoromethyl‐containing tetrahydrofuran‐ring and linear ketones in a divergent fashion. State‐of‐the‐art dispersion‐corrected DFT calculations strongly support the proposed mechanistic pathway for this novel transformation.